Sosialisasi Penggunaan Alat Pelindung Diri (APD) Pada Petani di Desa Songkar Moyo Utara - Rafi'ah; Iga Maliga; Ana Lestari (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Working as a farmer is a profession that has many risks with various kinds of dangers. One way that farmers can protect themselves from these potential hazards is to use Personal Protective Equipment (PPE). This community service aimed to increase farmers about the importance of using PPE when working. The method of community service was counselling through lectures and discussions conducted on farmers. This socialization activity was carried out in June 2021 by involving 20 farmers. The result showed that the level of knowledge of farmers about the use of PPE when working was still low, with a percentage of 15%. This service activity was hoped to increase the knowledge and awareness of farmers about the importance of using PPE when carrying out agricultural activities to prevent work consequences and work accidents.